PENGARUH PROFITABILITAS DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rizka Azwar, Sabina Jannatin; Oktaryani, G.A Sri (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine the influence of profitability and growth opportunities on company value in property and real estate sector companies listed on the Indonesia Stock Exchange. This research is a quantitative research that is associative. Samples were taken using the purposive sampling technique. In this study, the research sample amounted to 29 companies from 66 property and real estate companies listed on the Indonesia Stock Exchange (IDX) 2021-2023, so that the research data analyzed amounted to 87 observations. The panel data analysis method in this study is multiple linear regression analysis using Eviews version 12. The results of this study show that profitability has a positive and significant effect on the company's value. Meanwhile, growth opportunities have no effect on the company's value. From the results of this study, it is hoped that prospective investors need to pay attention to the company's growth opportunities carefully, because high asset growth does not always guarantee an increase in the company's value. And for companies, it is hoped that from the results of this study, companies will consider managing growth opportunities wisely so that growth can be controlled without causing risks